La2O2S Catalyst for Catalytic Reduction of SO2 with CO in the Presence of O2 - Zhu, Yunfeng; Ma, Zhi (Asian Journal of Chemistry, 2012)
Catalytic reduction of SO2 to sulphur by CO was investigated over La2O2S catalyst. It exhibited outstanding activity in the oxygen-free atmosphere and was inactivated in the presence of oxygen. The life decreased as the oxygen concentration increased, but increased as the reaction temperature increased. The increasing reaction temperature could prolong the life in a certain degree. The catalyst was characterized by XRD, TEM, XPS and BET, the phase structure of La2O2S is very stable; S2- species on the catalyst surface is an active species for SO2 reduction. The inactivation of La2O2S is probably caused by the sulfation of catalyst surface, not by the phase structure changes.